High-level athletes` motivation for sport and susceptibility to doping: The mediating role of eating behaviours - Scoffier-Mériaux, S.; d`Arripe-Longueville, F.; Woodman, T.; Lentillon-Kaestner, V.; Corrion, K. (European Journal of Sport Science, 2021)
Both doping (e.g., Hodge et al., 2013) and eating behaviours (e.g., Hagger, Chatzisarantis, & Harris, 2006) have been studied independently within the SDT framework, but no research has examined these variables concomitantly to better understand the relationships between motivation for sport and doping variables. We therefore examined the mediating role of eating behaviour in the relationship between SDT constructs for sport motivation and athletes` susceptibility to doping. Bootstrapped mediation analyses were performed for 171 male and female athletes with competitive experience in various sports. The analyses revealed that healthy eating behaviours significantly mediated the relationship between SDT motivational constructs and susceptibility to doping. The findings enrich our theoretical understanding of how the SDT approach to motivation for sport might provide insight into the susceptibility to doping; that is, through the potential mediating role of healthy eating behaviours. Finally, the potential central position of eating behaviours in the motivation-doping relationship opens up a potential swathe of novel research, with investigations into eating behaviours at the forefront of future research on the psychology of doping.